Effects of shear on the lamellar phase of a dialkyl cationic surfactant - Soubiran, L; Staples, E; Tucker, I; Penfold, J; Creeth, A (2001)
The effect of shear on the lamellar phase of the dialkyl cationic surfactant dihardened tallow dimethylammonium chloride has been determined using small-angle neutron scattering rheological measurements, and conductivity. We demonstrate that the formation of multilamelllar vesicles from rigid electrostatically charged membranes shows many of the features seen in the more flexible membrane systems previously studied. A shear-induced transition from an aligned lamellar phase to multilamellar vesicles has been observed, and the kinetics of the conductivity change associated with this shear induced transition has been characterized. The time invariant states that were characterized were also compared with the earlier results of Diat et al. on the mixture of sodium dodecyl sulfate, pentanol, and dodecane. For the latter system a second transition was observed at a higher shear rate, separating the vesicular state from a well-oriented lamellae state. This third time invariant state has not been observed for the system reported here. This difference in the phase behavior is discussed in terms of the coupling between the shear-induced deformation of the multilamellar vesicle and the interaction between membranes, which is different for the two systems.